2021
DOI: 10.3897/folmed.63.e60938
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Intranasal Versus Intravenous Lorazepam in the Management of Acute Seizure in Children

Abstract: Introduction: The acute seizure in childhood is a medical emergency which is usually managed by benzodiazepines used as a first line of therapy. There are no strict guidelines of using intranasal lorazepam in India. Many paediatricians use it in an emergency situation as it is inexpensive, easy to administer and even treatment can be started at home. Very few studies are available to compare efficacy and safety of intravenous lorazepam with intranasal lorazepam in childhood seizure, though both routes have com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previous studies, however, have suggested that IN midazolam (0.2 mg/kg/dose) is more effective than rectal diazepam (0.5 mg/kg/dose) ( 35 37 ). McTague et al highlighted that in general buccal and IN application of ASMs resulted in similar seizure cessation rates as IV-applied ASMs ( 15 , 38 44 ). The anticonvulsant effect of sublingual lorazepam has been reported to start with a delay of about 20 min after drug application, and this treatment is therefore inappropriate for acute SE treatment ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies, however, have suggested that IN midazolam (0.2 mg/kg/dose) is more effective than rectal diazepam (0.5 mg/kg/dose) ( 35 37 ). McTague et al highlighted that in general buccal and IN application of ASMs resulted in similar seizure cessation rates as IV-applied ASMs ( 15 , 38 44 ). The anticonvulsant effect of sublingual lorazepam has been reported to start with a delay of about 20 min after drug application, and this treatment is therefore inappropriate for acute SE treatment ( 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lorazepam is available as tablets (0.5, 1, and 2 mg), an intravenous injection (2 and 4 mg/mL), an oral concentrate (2 mg/mL) [ 71 – 73 ], and a sublingual tablet, which is available in Europe and Canada. Two studies have shown that up to 4-mg doses of intravenous and a non-atomized intranasal solution of lorazepam (directly instilled into one nostril) produced remission of acute seizure within 10 min in pediatric populations (aged 5–14 years) in India [ 74 , 75 ]. The effectiveness (time to onset, duration) of lorazepam for seizure clusters specifically has not been formally confirmed in large clinical trials [ 62 ].…”
Section: Use Of Other Treatments For Seizure Clustersmentioning
confidence: 99%
“…Finally, lorazepam is reported to be 4 to 6 times less lipid soluble than midazolam and diazepam, and it has been found to have a peak effect time of 30 min and a half-life of 18.5 h after intranasal administration [ 65 , 66 ]. Intranasal lorazepam has been evaluated in studies in children and found to be comparable to intravenous lorazepam, with the same median onset time [ 67 , 68 ]. However, it is uncertain whether any benefit is obtained from lorazepam compared with midazolam, other than perhaps having an extended duration of action and being easier to formulate than diazepam.…”
Section: Relationships Between the Nose And Epilepsymentioning
confidence: 99%